Frequent CpG island methylation: a risk factor in the progression of traditional serrated adenoma of the colorectum - Shi, Yan (Int J Clin Exp Pathol, 2017)
Background: Traditional serrated adenoma (TSA) features a unique serrated configuration because it involves two cell types: tall and short columnar cells. The serrated neoplasia pathway is related to the carcinogenesis of colorectal cancer. CpG island methylator phenotype-high (CIMP-high) is a unique genetic alteration in this pathway. Materials and Methods: This study investigated the prevalence and level of methylation and CIMP in 30 TSA cases. The tall and short cells in 28 TSAs were separated by microdissection. Methylation-specific PCR was performed to detect the methylation of MGMT, MLH1, P14, P16, MINT1, MINT2 and MINT31. Results: Overall, 30 cases presented CIMP-high, and the prevalence of CIMP-high was 100% (30/30) in tall cells and 93% (28/30) in short cells. Conclusions: No significant difference was found between tall and short columnar cells. The relationship between methylation and clinicopathological characters remains to be established.